The Important Role of the Organization of Islamic Cooperation in Resolving Investor-State Dispute Settlements through the Perspective of International Law - Adeline Anindya Rusdianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Organization of Islamic Cooperation (“OIC”) seeks to enhance economic collaboration between its member states, as outlined in the OIC Charter. Its key efforts is the Agreement for Promotion, Protection and Guarantee of Investments among OIC Member States (“OIC Investment Agreement”), which provides safeguards for cross-border investments and outlines procedures for resolving disputes between investor-states. Article 17 of the Agreement allows for dispute resolution through conciliation or arbitration. However, the lack of a dedicated dispute resolution body and clear procedural mechanisms has led to uncertainty and differing interpretations, weakening its effectiveness. This article explores the OIC’s role in investor-state dispute settlement (ISDS) under the Investment Agreement. It highlights the need for a more structured and permanent mechanism to ensure fair and consistent resolution of ISDS cases, in alignment with the objectives of the OIC Charter.